Rancang bangun sistem monitoring curah hujan berbasis internet of things - Muhamad Fajar; Adhitia Erfina (Computer Science and Information Technology, 2023)
Weather information is an integral part of everyday life. To anticipate extreme weather or weather that always changes from time to time and from place to place, good facilities are needed such as weather measurement equipment, one of which is a rain gauge sensor to monitor weather conditions based on the Internet of things (IoT). Can detect the intensity of rainwater and then the resulting data is sent to the website interface via the Arduino microcontroller and the ESP8266 WiFi module. The test results show that this system can carry out an IoT-based monitoring process in real time with an average delay of around 3 seconds.